2000
DOI: 10.1104/pp.122.1.215
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Regulation of Monoterpene Biosynthesis in the Glandular Trichomes of Peppermint

Abstract: Monoterpene production in peppermint (Mentha ؋ piperita L.) glandular trichomes is determined by the rate of biosynthesis, as determined by 14

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
130
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(143 citation statements)
references
References 48 publications
9
130
0
4
Order By: Relevance
“…In a developmental manner, juvenile leaves, which are no older than 2 weeks postsprouting, have the highest steady- state level of QH6 mRNA. This is similar to the findings from peppermint in which monoterpenes were found to be synthesized only in 12-to 20-d-old leaves that were not yet fully expanded (Mihaliak et al, 1991;Gershenzon et al, 2000;McConkey et al, 2000). This rapid decline during development is supported by Tellez et al (1999), who found that in leaves of 4-month-old A. annua plants, no ␤-pinene could be detected, whereas ␣-pinene represented as much as 26.7% of the total volatiles extracted.…”
Section: Spatial and Temporal Characteristics Of (؊)-␤-Pinene Biosyntsupporting
confidence: 76%
See 1 more Smart Citation
“…In a developmental manner, juvenile leaves, which are no older than 2 weeks postsprouting, have the highest steady- state level of QH6 mRNA. This is similar to the findings from peppermint in which monoterpenes were found to be synthesized only in 12-to 20-d-old leaves that were not yet fully expanded (Mihaliak et al, 1991;Gershenzon et al, 2000;McConkey et al, 2000). This rapid decline during development is supported by Tellez et al (1999), who found that in leaves of 4-month-old A. annua plants, no ␤-pinene could be detected, whereas ␣-pinene represented as much as 26.7% of the total volatiles extracted.…”
Section: Spatial and Temporal Characteristics Of (؊)-␤-Pinene Biosyntsupporting
confidence: 76%
“…Borg-Karlson et al, 1994). In different developmental stages of peppermint, coincident temporal change in enzyme activities, enzyme protein levels, and steadystate transcript abundances of monoterpene synthases was demonstrated, indicating that most of the monoterpene synthases in this plant are regulated at the level of gene expression (Gershenzon et al, 2000;McConkey et al, 2000).…”
mentioning
confidence: 99%
“…This is the first study, to our knowledge, that demonstrates the constitutive and induced activity of terpenoid synthases at a tissue-specific level in a gymnosperm system. Enzymatic and molecular studies of terpenoids at the tissue-specific level have previously been reported only in some angiosperm systems, the glandular trichomes of Mentha ϫ piperita (McConkey et al, 2000), the trichomes of Nicotiana glutinosa (Guo and Wagner, 1995), or the scentproducing floral tissues of Clarkia breweri (Dudareva et al, 1996). The results described here justify future analysis of MeJA-induced TD differentiation and regulation of terpenoid biosynthesis in spruce at the cellular and subcellular level to elucidate the control mechanisms responsible for such localized expression.…”
Section: )mentioning
confidence: 99%
“…Moreover, as these tissues contain many of the enzymes and significantly express many of the genes involved in the production of such metabolites, the isolation of secretory cells has greatly contributed to characterization of many of the enzymes and genes involved in the formation of many plant natural products in peppermint, sweet and lemon basil, as well as tomato and other crops (Fridman et al, 2005;Gang et al, 2002;Iijima et al, 2004a,b;McConkey et al, 2000). The following sections describe the biosynthesis of plant-derived flavor molecules grouped by their biogenetic origin.…”
Section: Biosynthetic Pathwaysmentioning
confidence: 99%